Poetry, Power, and Language: Rereading Arabic Metaphors and Their Implications for Arabic Language Education in Indonesia - Maman Dzul'iman; Irfan Hania (LISANIA: Journal of Arabic Education and Literature, 2025)
This study investigates the historical evolution of metaphor in Arabic poetry, from the classical to the modern era, and explores its implications for Arabic language instruction in Indonesia. Utilizing a qualitative approach, the research analyzes a purposive selection of ten major poems from the classical and modern eras, chosen for their thematic representativeness of power dynamics and social change. The analysis integrates semantic-rhetorical, intertextual, and critical discourse frameworks to uncover shifting metaphorical functions. The findings reveal that classical metaphors were rooted in natural and spiritual imagery, reinforcing social values, divine order, and political legitimacy. In contrast, modern metaphors reflect sociopolitical critique, existential anxiety, and resistance to colonial and authoritarian regimes. This transformation mirrors broader cultural and ideological shifts within Arab societies. By tracing this evolution, the study demonstrates that metaphors are not merely decorative but function as cognitive and ideological tools that encode historical consciousness. The research further argues that incorporating metaphor-rich poetry into Arabic language education in Indonesia enhances learners' interpretive and expressive skills. A context-based, thematic pedagogical model is proposed, integrating classical and modern texts to foster critical reading (qirā’ah) and creative writing (kitābah) skills. While limited by its theoretical scope and lack of empirical classroom testing, this research offers a novel framework that bridges the gap between literary evolution and curriculum development, transforming metaphors from linguistic ornaments into instruments of cultural and critical literacy.